Exploring the Multidimensional Poverty Index: National and Children’s Dimensions in Malaysia - Mohd Khairi Ismail; Suhaiza Hanim Mohamad Zailani; Muhamad Zahid Muhamad; Nurul Ashikin Alias; Muhammad Nooraiman Zailani (World)
The COVID-19 pandemic has exacerbated the challenges faced by children in Malaysia, particularly in terms of poverty and hardship. This has led to concerns about the long-term impact on children’s welfare, particularly in terms of educational and economic inequalities. The multidimensional nature of poverty is often overlooked in public policy discussions, and most countries use National Multidimensional Poverty Indices (MPIs) to define child poverty levels within a nation. This article aims to compare the results of a child-specific Multidimensional Poverty Index (MPI) with those of a household-specific MPI, considering the uncertainty surrounding the capacity of Household MPIs to accurately identify multidimensionally impoverished children. This study, conducted in Pahang, Malaysia, uses survey data to examine the multidimensional child poverty status and its dynamic changes. The modified child poverty headcount ratio, using the Alkire–Foster methodology, evaluates both the traditional headcount ratio of child poverty and the mean level of deprivation among disadvantaged children. The results indicate low poverty rates in Pahang and its districts. Increased policy attention has been called for due to rising unemployment among parents and the increasing number of bereaved children due to the pandemic.